INFORMATION SECURITY AWARENESS FRAMEWORK : A CASE STUDY FOR BANKING EMPLOYEES IN SUDAN - Merghani Izzedlin Merghani, 1975-, author; Rasimah Che Mohd. Yusoff, Dr., supervisor; Sekolah Informatiks Termaju (Kuala Lumpur : Universiti Teknologi Malaysia, 2016)
Thesis (Sarjana Sains (Jaminan Maklumat))-Universiti Teknologi Malaysia, 2016